Identifying environmentally conscious apparel acquisition behaviors among eco-conscious consumers - Hiller Connell, Kim Y.; Sontag, M. Suzanne (International Textile and Apparel Association, Inc., 2011)
The last few years has seen significant increased mass media coverage of environmentally conscious apparel consumption. However, despite the increased attention in mass media, eco-conscious apparel acquisition remains relatively under-researched from a scientific perspective. As the vulnerability of the natural environment continues and the encouragement of sustainable consumption patterns becomes even more important, this lack of both depth and breadth in knowledge about eco-conscious apparel acquisition needs addressing. The overall purpose of this research study is to expand the knowledge base of eco-conscious apparel consumption by identifying specific apparel acquisition behaviors that eco-conscious consumers engage in as they aim to lower the environmental impact of their apparel consumption.
Keywords: Eco-conscious; Apparel; Acquisition; Behavior